4x-3(2x-7)=9+5(x-2)

Simple and best practice solution for 4x-3(2x-7)=9+5(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(2x-7)=9+5(x-2) equation:


Simplifying
4x + -3(2x + -7) = 9 + 5(x + -2)

Reorder the terms:
4x + -3(-7 + 2x) = 9 + 5(x + -2)
4x + (-7 * -3 + 2x * -3) = 9 + 5(x + -2)
4x + (21 + -6x) = 9 + 5(x + -2)

Reorder the terms:
21 + 4x + -6x = 9 + 5(x + -2)

Combine like terms: 4x + -6x = -2x
21 + -2x = 9 + 5(x + -2)

Reorder the terms:
21 + -2x = 9 + 5(-2 + x)
21 + -2x = 9 + (-2 * 5 + x * 5)
21 + -2x = 9 + (-10 + 5x)

Combine like terms: 9 + -10 = -1
21 + -2x = -1 + 5x

Solving
21 + -2x = -1 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
21 + -2x + -5x = -1 + 5x + -5x

Combine like terms: -2x + -5x = -7x
21 + -7x = -1 + 5x + -5x

Combine like terms: 5x + -5x = 0
21 + -7x = -1 + 0
21 + -7x = -1

Add '-21' to each side of the equation.
21 + -21 + -7x = -1 + -21

Combine like terms: 21 + -21 = 0
0 + -7x = -1 + -21
-7x = -1 + -21

Combine like terms: -1 + -21 = -22
-7x = -22

Divide each side by '-7'.
x = 3.142857143

Simplifying
x = 3.142857143

See similar equations:

| 4x+23+8x+7= | | -4(2x-3)=2(7x-5) | | x^3(9)=81 | | 8-2x=3x+43 | | 6x-32=0 | | 7x+9=-79 | | br-1+6r=11 | | 5(k+3)=2(k+7)-5 | | 2-3a+7=8a+3-a | | 16x(2x-9)=4(8x+8) | | 4x+6=74 | | 16y=180 | | 2m+7=2m-9 | | 6x+58=0 | | 2(x-3)=-24 | | 3(y-2)=y+8 | | 10x-3=6x+39 | | a=-5n+2n | | 2x+1=53 | | 5x+64=180 | | 7(11x-8)=77x-10 | | 13.0x-180forx=50 | | 8g+6=9g-10 | | x+77+x+62+45=180 | | 2(3x-7)=(5x-6) | | 9(x+5)=108 | | (2x+43)=(2x-3) | | X+-16=9 | | 13x-1=8x+39 | | n^2=-n | | 3*2-5+4*3-8+5*2= | | x-4+1=-3-x |

Equations solver categories